Inhibition of human serum peroxidasein patients with thalassemiaby fournewly synthesizedsulfonamide derivatives - Israa Zainal (Al-Mustansiriyah Journal of Science, 2019)
This study was aimed to determine the in vitro effects of four newly synthesized sulfonamide derivatives(Sulfacetamid ,Sulfanilamid, sulfadiazine, sulphamethoxazole)on human serum peroxidase activity in patients with thalassemia compared to healthy subjects.Total protein,the peroxidase activity was increased non – significantly(p≥ 0.0001) and the specific activity of the enzyme was increased significantly(p≤ 0.0001) in the sera of patients with thalassemia compared to healthy subjects and the results revealed that all used compoundscaused (moderate to good) inhibitory effecton the peroxidase activity and the highest inhibition percent were obtained at (0.18 gm/ml from Sulphacetamide ,0.01gm/ml from Sulphamethaxazole,0.05gm/ml from Sulphadizine and 0.02gm/mlfrom Sulphamide).This study also determined the kinetic parameters (Km,Ki, Vmax and Vmax i) at different concentrations from substrate and each inhibitor under the same conditions by using Lineweaver-Burk equation and the results indicated that the level of Km was not affected by adding the inhibitor to the enzyme reaction and equal to the level of Ki while the levels of Vmax were decreased when the reaction of enzyme include the inhibitor.Finally the type of inhibition was found as non-competitive inhibion to the all used sulfonamide derivatives,this type of inhibition is characterized by its effect on the maximum velocity and is obtained when the inhibitor and the substratewere linked to different sites at enzyme .